2013
DOI: 10.1186/1471-2229-13-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics of a generalist parasitic plant: Laser microdissection of host-parasite interface reveals host-specific patterns of parasite gene expression

Abstract: BackgroundOrobanchaceae is the only plant family with members representing the full range of parasitic lifestyles plus a free-living lineage sister to all parasitic lineages, Lindenbergia. A generalist member of this family, and an important parasitic plant model, Triphysaria versicolor regularly feeds upon a wide range of host plants. Here, we compare de novo assembled transcriptomes generated from laser micro-dissected tissues at the host-parasite interface to uncover details of the largely uncharacterized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 84 publications
2
81
0
2
Order By: Relevance
“…Interestingly, the earliest expression modulation occurs with genes related to calmodulin binding and oxidoreductase activity ( Figure 2C), suggesting that calcium and reactive oxygen species (ROS)-related signaling may be triggered in the early stage of development. Indeed, the involvement of ROS in haustorium initiation signaling has been proposed (Kim et al, 1998;Ngo et al, 2013;Matvienko et al, 2001aMatvienko et al, , 2001bHonaas et al, 2013;Bandaranayake et al, 2010;Yang et al, 2015). Consistent with other published studies, our analysis identified homologous genes, which were previously identified as DMBQ-responsive genes in T. versicolor, such as QR2 and Pirin, that are upregulated after DMBQ treatment in P. japonicum, suggesting that gene expression profiles are conserved among Orobanchaceae species during haustorium formation.…”
Section: Comprehensive Survey Of Genes Involved In the Earlysupporting
confidence: 89%
“…Interestingly, the earliest expression modulation occurs with genes related to calmodulin binding and oxidoreductase activity ( Figure 2C), suggesting that calcium and reactive oxygen species (ROS)-related signaling may be triggered in the early stage of development. Indeed, the involvement of ROS in haustorium initiation signaling has been proposed (Kim et al, 1998;Ngo et al, 2013;Matvienko et al, 2001aMatvienko et al, , 2001bHonaas et al, 2013;Bandaranayake et al, 2010;Yang et al, 2015). Consistent with other published studies, our analysis identified homologous genes, which were previously identified as DMBQ-responsive genes in T. versicolor, such as QR2 and Pirin, that are upregulated after DMBQ treatment in P. japonicum, suggesting that gene expression profiles are conserved among Orobanchaceae species during haustorium formation.…”
Section: Comprehensive Survey Of Genes Involved In the Earlysupporting
confidence: 89%
“…We thus took these factors into account in our pipeline and carefully evaluated each potential HGT candidate with additional data to identify and reduce potential sources of error. We focus on potentially functional genes acquired by parasitic plants by concentrating our search on extensive transcriptome evidence for members of Orobanchaceae grown on host plants with known genome sequences (30,32,33); in addition to greatly improving the accuracy of HGT identification, it offers the opportunity to identify the expression patterns associated with genes derived from HGT events (28).…”
Section: Significancementioning
confidence: 99%
“…Genes associated with stress responses were also found to be up-regulated in roots of a root parasite after contact with a host plant (Torres et al, 2005;Honaas et al, 2013). Thus, it can be hypothesized that parasitic plants recruit defense-related genes for host recognition.…”
Section: Recruitment Of Genes Relating To Responses To Stimuli and Cementioning
confidence: 99%
“…Expansin cell wall modulators were identified as core regulators of parasitism in the root parasites Striga spp. and T. versicolor (O'Malley and Lynn, 2000;Vaughn, 2002;Honaas et al, 2013). However, expansin regulation of plant parasitism might be a more complex phenomenon in the stem parasite Cuscuta spp., as different genes encoding expansins were represented among both the up-regulated and down-regulated genes.…”
Section: Recruitment Of Genes Relating To Responses To Stimuli and Cementioning
confidence: 99%
See 1 more Smart Citation